Detection of new SHV-12, SHV-5 and SHV-2a variants of extended spectrum Beta-lactamase in Klebsiella pneumoniae in Egypt - Newire, Enas A (BioMed Central, 2013)
BACKGROUND: Klebsiella pneumoniae outbreaks possessing extended-spectrum β-lactamase- (ESBL) mediated resistance to third-generation cephalosporins have increased significantly in hospital and community settings worldwide. The study objective was to characterize prevalent genetic determinants of TEM, SHV and CTX-M types ESBL activity in K. pneumoniae isolates from Egypt. METHODS: Sixty five ESBL-producing K. pneumoniae strains, isolated from nosocomial and community-acquired infections from 10 Egyptian University hospitals (2000–2003), were confirmed with double disc-synergy method and E-test. blaTEM, blaSHV and blaCTX-m genes were identified by PCR and DNA sequencing. Pulsed-field gel electrophoresis (PFGE) was conducted for genotyping. RESULTS: All isolates displayed ceftazidime and cefotaxime resistance. blaTEM and blaSHV genes were detected in 98% of the isolates’ genomes, while 11% carried blaCTX-m. DNA sequencing revealed plasmid-borne SHV-12,-5,-2a (17%), CTX-m-15 (11%), and TEM-1 (10%) prevalence. Among SHV-12 (n=8), one isolate displayed 100% blaSHV-12 amino acid identity, while others had various point mutations: T17G (Leu to Arg, position 6 of the enzyme: n=2); A8T and A10G (Tyr and Ile to Phe and Val, positions 3 and 4, respectively: n=4), and; A703G (Lys to Glu 235: n=1). SHV-5 and SHV-2a variants were identified in three isolates: T17G (n=1); A703G and G705A (Ser and Lys to Gly and Glu: n=1); multiple mutations at A8T, A10G, T17G, A703G and G705A (n=1). Remarkably, 57% of community-acquired isolates carried CTX-m-15. PFGE demonstrated four distinct genetic clusters, grouping strains of different genetic backgrounds. CONCLUSIONS: This is the first study demonstrating the occurrence of SHV-12, SHV-5 and SHV-2a variants in Egypt, indicating the spread of class A ESBL in K. pneumoniae through different mechanisms.